2020
DOI: 10.1080/02640414.2020.1841396
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between changes in self-reported physical activity, sedentary behaviour and health during the coronavirus (COVID-19) pandemic in France and Switzerland

Abstract: To assess whether changes in physical activity and sedentary behaviour during the COVID-19 lockdown are associated with changes in mental and physical health. Observational longitudinal study. Participants living in France or Switzerland responded to online questionnaires measuring physical activity, physical and mental health, anxiety, and depressive symptoms. Paired sample t-tests were used to assess differences in physical activity and sedentary behaviour before and during lockdown. Multiple linear regressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
252
3
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(333 citation statements)
references
References 21 publications
38
252
3
13
Order By: Relevance
“…Our observation of lower levels of physical activity during lockdown is in line with some other reports on adults [1] and children [2] that indicate a decrease in vigorous physical activity and an increase in sedentariness during this time. However, there is also evidence from research with adults and from consumer reports that participation in online exercise classes, home workouts, and time spent walking increased during lockdown [1,52]. Our finding of a decrease in physical activity could suggest that such online or home-based physical activities are less accessible to older people.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observation of lower levels of physical activity during lockdown is in line with some other reports on adults [1] and children [2] that indicate a decrease in vigorous physical activity and an increase in sedentariness during this time. However, there is also evidence from research with adults and from consumer reports that participation in online exercise classes, home workouts, and time spent walking increased during lockdown [1,52]. Our finding of a decrease in physical activity could suggest that such online or home-based physical activities are less accessible to older people.…”
Section: Discussionsupporting
confidence: 93%
“…Cross-sectional studies of diverse populations have documented the many consequences of lockdowns across the globe. These include reduced levels of physical activity [1,2], poorer diet [3], and an increased prevalence of sleep problems [4]. Various psychosocial consequences of lockdown have also been reported, including higher rates of loneliness [5,6], less social cohesion (particularly in deprived communities) [7], more mental health difficulties, and a decrease in psychological wellbeing [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although PA is predicted to be reduced by COVID-19 (Roschel et al, 2020) data thus far appears equivocal. Maugeri, et al (Maugeri et al, 2020) observed a reduction in PA and energy expenditure across age groups in Italy whereas (Cheval et al, 2020) observed increased sedentary time, decreased vigorous PA but an increase in walking time and moderate PA in younger adults. This research will aid public health practitioners in understanding where support is needed, not only in the coming weeks and months following the COVID-19 pandemic, but also in the event of future lockdown scenarios.…”
Section: The Present Studymentioning
confidence: 92%
“…Moreover, given the residential situation of many participants (Table 4), more time was spent in gardens, as gardening was the second most popular change to activities. However, despite maintaining PA levels, there is strong evidence that sitting time increased for both sexes, indicating an increase in sedentary behaviour which has previously been associated with decreased physical and mental health (Cheval et al, 2020).…”
Section: Physical Activity and Sedentary Behaviourmentioning
confidence: 96%
See 1 more Smart Citation